Test-retest Reliability of the Persian version of the questionnaire Affordances in the Home Environment for Motor Development-Infant Scale and its Relation with Infant Movement - Somayeh Kavousipor; Saeedeh Fallahi Nejad; Elham Jamali; Saghar Zandian Ghahfarokhi (Shiraz University of Medical Sciences, 2016)
Background: Since the home environment is the first place on which children (particularly, those under two years of experience and development) are highly dependent, the existence of a questionnaire for evaluating this environment is necessary. Therefore, in the present study, the test-retest reliability of the Affordance in the Home Environment for Motor Development-Infant Scale (AHEMD-IS) is reported. Methods: The aim to this study was to investigate certain psychometric characteristics of the AHEMD-IS. Therefore, 112 mother-infant (3-18 months old infants) couples participated in this study. The AHEMD and the Ages and Stages Questionnaire (ASQ) were completed by all the participants and 46 participants re-completed the questionnaire for investigating their repeatability. Finally, the collected data were analyzed using tests of correlation coefficients in SPSS-21. Results: The findings of the AHEMD-IS enjoys acceptable reliability. The intraclass coefficient (ICC) of the total score of the questionnaire was 0.78, the intraclass coefficient of physical space was 0.96, the intra-class coefficient of a variety of stimuli was 0.93, the intra-class coefficient of the gross motor toys was 0.93, and the intra-class coefficient for fine motor toys was 0.96. In addition, the concurrent validity indicated that the section on the diversity of stimuli and toys for fine movements had a significant correlation with the motor sections of the ASQ (P<0.5). Conclusion: The results of this study indicated that the AHEMD-IS is a reliable instrument for 3-18 month old infants.